Stable cross-sectional dimensions for navigation channel in the estuary of Sangatta River, Indonesia - Sutarto Tommy (EDP Sciences, 2021)
The objectives of this study are: 1) to capture the existing condition of the river channel in Sangatta River estuary, including the bathymetry of the river bed, and the cross-sectional dimensions of the river, 2) to design a stable navigation channel in Sangatta River estuary that allows less maintenance dredging and improves navigability of the channel during a critical condition when the water level is at the lowest, and 3) to test the effectiveness of the stable cross section in term of the availability of navigable depth. This research is divided into five stages, namely: 1) preparatory stage and preliminary survey, 2) main surveys, 3) hydrological and hydraulic analysis, 4) waterway design, and 5) dredging plan. The hydraulic analysis also includes determining the water level and depth profiles before and after dredging. HEC-RAS software is used to simulate, for each month, the water level and depth profiles in the channel at a critical condition when the sea water level is at low water spring (LWS) coincides with the river flow of 50% probability of occurrence, Q50. A stable channel for Sangatta River estuary is characterized with a bed slope, S = 0.00015, a flow depth, D = 3.6 m, a bed width, b = 76.3 m and a sidewall slope, m = 1.5. The simulation results show that the stable cross sections of the river provide sufficient water depth for navigation, even during the critical condition.